2000
DOI: 10.1016/s0022-2275(20)31998-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of phospholipid transfer protein in human plasma: presence of two forms of phospholipid transfer protein, one catalytically active and the other inactive

Abstract: Plasma phospholipid transfer protein (PLTP) plays an important role in the maintenance of plasma highdensity lipoprotein (HDL) content and remodeling of HDL in the circulation. In the present study we have used different fractionation methods to investigate the distribution of PLTP in human plasma. A novel enzyme-linked immunosorbent assay developed during the study allowed for simultaneous assessment of both PLTP mass and activity in the fractions obtained. Size-exclusion chromatography and plasma fractionati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 38 publications
(34 reference statements)
2
26
0
Order By: Relevance
“…As the localization of PLTP and CETP in the lower molecular weight range differed in such a way that two different particles could be separated by 2D-GGE, with the PLTP spot having higher molecular mass and slow HDL mobility, these particles may represent either lipid-complexed proteins or homodimers. Oka et al (36) have demonstrated the presence of large (12-to 14-nm) particles with PLTP immunoreactivity. These particles carry an inactive form of PLTP, whereas the active form of PLTP was associated with smaller, 9-to 11-nm particles.…”
Section: Discussionmentioning
confidence: 98%
“…As the localization of PLTP and CETP in the lower molecular weight range differed in such a way that two different particles could be separated by 2D-GGE, with the PLTP spot having higher molecular mass and slow HDL mobility, these particles may represent either lipid-complexed proteins or homodimers. Oka et al (36) have demonstrated the presence of large (12-to 14-nm) particles with PLTP immunoreactivity. These particles carry an inactive form of PLTP, whereas the active form of PLTP was associated with smaller, 9-to 11-nm particles.…”
Section: Discussionmentioning
confidence: 98%
“…An alternative explanation for the presence of inactive and active PLTP may be that the conformation of PLTP may differ when it is associated with larger particles as compared with smaller ones, resulting in a loss of transfer activity as suggested by Oka et al (4). The binding of PLTP to particles with a certain radius of curvature may affect the conformation of PLTP in such a way that binding or efficient transfer of lipid is impeded.…”
Section: Discussionmentioning
confidence: 99%
“…Oka et al (3) carried out another study using a double monoclonal sandwich ELISA and also reported no correlation between PLTP mass and activity in a group of 132 Japanese subjects. Oka et al (4), using the double monoclonal sandwich ELISA system for detection of PLTP mass, went on to analyze the mass and activity of PLTP in lipoprotein fractions separated by fast protein liquid chromatography (FPLC). They reported a large discrepancy between the distribution of mass as compared with that of PLTP activity, with substantial mass being present in the LDL and very large HDL region and the majority of the activity being found in the region of small HDL.…”
mentioning
confidence: 99%
“…Given the fact that the protein content of normal rabbit cerebrospinal fluid is approximately two orders of magnitude lower than that of plasma (41) and assuming a normal specific activity of PLTP in cerebrospinal fluid, we estimate the relative PLTP concentration of rabbit cerebrospinal fluid to exceed that of plasma by at least 20-fold. If the cerebrospinal fluid, like plasma (48), were to contain both active and inactive forms of PLTP, extrapolation from activity to PLTP mass data would be further complicated. Even the relatively high PLTP activity in the cere- brospinal fluid need not be due necessarily to local PLTP synthesis, but could reflect efficient active transport from plasma.…”
Section: Discussionmentioning
confidence: 99%